Virtual Reality High-Intensity Interval Training Exergaming Compared to Traditional High-Intensity Circuit Training Among Medical Students: Pilot Crossover Study - Pietro Merola; Marcos Barros Cardoso; Gabriel Barreto; Matheus Carvalho Chagas; Luana Farias Oliveira Saunders; Bryan Saunders; Danilo Cortozi Berton (JMIR Serious Games)
Abstract BackgroundThis study evaluated the effectiveness of a virtual reality (VR) high-intensity interval training (HIIT) boxing protocol compared to traditional high-intensity circuit training (HICT) in improving exercise motivation, engagement, and physiological responses among 30 healthy medical students. ObjectiveThe purpose was to compare the VR HIIT protocol, which involved using an Oculus Quest 2 for a futuristic exoskeleton game experience, with a traditional 12-exercise HICT. MethodsIn total, 30 medical students engaged in both VR HIIT, using an Oculus Quest 2 for a futuristic exoskeleton game experience, and a traditional 12-exercise HICT. Metrics included heart rate (HR) and blood lactate levels before and after exercise alongside ratings of perceived exertion and the Situational Motivation Scale. ResultsVR HIIT showed significantly higher mean HR (mean 161, SD 15 vs mean 144, SD 11 bpm; dPdPdPdPdP ConclusionsVR HIIT significantly enhances physiological parameters while maintaining intrinsic motivation, making it a viable alternative to traditional HICT. However, the short-term nature of this study is a limitation, and future research should explore the long-term engagement and therapeutic impacts of VR exercise in diverse and clinical populations.